Hubungan Perilaku Hidup Bersih Sehat (PHBS) dengan Kejadian Skabies di Pesantren Darul Istiqamah Manado - Janpri, Michael; Niode, Nurdjannah J.; Kairupan, Tara S. (Medical Scope Journal, 2025)
Abstract: Scabies is an infectious disease caused by the infestation of Sarcoptes scabiei var. Hominis, and ranks 3rd among the twelve most common diseases. One of the problem factors that cause the high rate of the spread of scabies, especially in dormitories or boarding schools, is the level of personal hygiene. This study aimed to determine the relationship between personal hygiene and the prevalence of scabies at Pesantren Darul Istiqamah Manado. This was an analytical study with a cross-sectional design. Samples were obtained by using total sampling method. Data were analyzed using the chi-square test. The results showed that there were 134 students at Pesantren Darul Istiqamah included in this study. Students that had good level of personal hygiene were as many as 82 people (61.2%) and those with poor level of personal hygiene were 52 people (38.8%). There were 60 students (44.8%) detected with scabies and 74 students (55.2%) not detected with scabies. The chi-square test obtained a p-value of <0.001 for the relationship between personal hygiene and the occurence of scabies. In conclusion, there is a significant relationship between personal hygiene and the occurence of scabies at Pesantren Darul Istiqamah Manado. Keywords: Islamic Boarding School; scabies; personal hygiene Abstrak: Skabies merupakan penyakit infeksi akibat infestasi Sarcoptes scabiei var. Hominis dan menempati peringkat ke-3 dari 12 penyakit tersering di Indonesia. Salah satu faktor permasalahan yang menyebabkan tingginya angka penyebaran skabies khususnya di asrama atau pondok pesantren ialah tingkat perilaku hidup bersih sehat (PHBS) yang rendah. Penelitian ini bertujuan untuk mengetahui hubungan PHBS dengan kejadian skabies di Pesantren Darul Istiqamah Manado. Jenis penelitian ialah analitik dengan desain potong lintang. Metode sampling menggunakan total sampling. Analisis data menggunakan uji chi-square. Hasil penelitian mendapatkan sebanyak 134 pelajar yang menjadi sampel penelitian. Di Pesantren Darul Istiqamah, pelajar yang memiliki tingkat PHBS baik sebanyak 82 orang (61,2%) dan tingkat PHBS buruk sebanyak 52 orang (38,8%). Terdapat 60 pelajar (44,8%) terdeteksi skabies dan 74 pelajar (55,2%) tidak terdeteksi skabies. Hasil uji chi-square mendapatkan nilai p<0,001 terhadap hubungan antara PHBS dengan kejadian skabies. Simpulan penelitian ini ialah terdapat hubungan bermakna antara perilaku hidup bersih sehat dengan kejadian skabies di Pesantren Darul Istiqamah Manado. Kata kunci: pesantren; kejadian skabies; perilaku hidup bersih sehat